Maintenance obligation: An analysis of civil and criminal liability - Steffen , Pablo Franciano; Jesus , Janaína Pereira de (Seven Editora, 2023)
The maintenance obligation, in the Brazilian legal system, finds support in the civil and criminal spheres, with the aim of preserving the maintenance of life in society of the individual, who, for reasons beyond his will, cannot sustain himself with his own effort. Hence, for the law, maintenance in the broad sense encompasses sustenance, clothing, education, medicines, etc. Based on these considerations, not forgetting to present the characteristics and classifications of alimony, the article proceeds to analyze the liability of the agent in the civil sphere, in which, in the face of non-compliance with the duty, the legislation provides for the possibility of civil imprisonment, which is used as a means of coercion. In the criminal sphere, the agent's excuse from aiding, whether in pecunia or in resources, to the family member who needs and is entitled to it, may constitute the crime of material abandonment provided for in article 244 of the Penal Code. To better understand, we sought to present the subjects who hold the right, as well as those who have the obligation. Finally, briefly, the possibility of applying criminal detraction in view of the fulfillment of the sentence of restriction of civil and criminal liberty was discussed. DOI:https://doi.org/10.56238/interdiinovationscrese-048